Implementasi Persuasion Theory Terhadap Hafalan Al-Qur’an Anak Cerebral Palsy melalui Platform Youtube - Anggreni Anggreni (LP. Ma'arif Janggan Magetan, 2024)
Cerebral palsy is one of the medical conditions that is often identified in infancy or early childhood and affects the development of movement and coordination of the body. This research uses qualitative methods with data collection techniques, namely online observation and documentation studies. Online observation and download of Naja Hudia Hafiz Indonesia RCTI 2019 video recording on Youtube. The results of this study found that first, the role of parents is very important in achieving children's memorization of the Qur'an. Tips made by Naja Hudia's parents in making children memorize the Qur'an are sincere towards the qadha of Allah; inviting orphans to the house; and using auditory methods that often listen to the Qur'an. Second, the use of the YouTube platform as a medium of persuasion has two paths, namely the central processing path and the peripheral processing path. So that the youtube platform can or cannot influence individuals in different ways, depending on individual characteristics and the message so that it is hoped that children with special needs will be able to change their mindset to be motivated by the success story of memorizing the Qur'an Naja Hudia which can be watched on the youtube platform.